2010
DOI: 10.1002/jso.21744
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lymphangiogenesis in primary tumor and draining lymph nodes during lymphatic metastasis of pancreatic head cancer

Abstract: Lymphangiogenesis in primary tumors and draining lymph nodes is essential for efficient spread of tumor cells through the lymphatic system. Thus, inhibition of lymphangiogenesis could limit lymphatic dissemination of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…We can predict a similar phenomenon in colorectal cancer as the level of VEGF-C was shown to be elevated in the blood serum of patients with colorectal cancer [19]. It has been hypothesized that lymph node lymph vessels can act as a metastatic niche for cancer cells [7], [8], [20], [21] and facilitate further metastatic transformation of the tumor cells. This might lead to therapy-resistant metastatic cancer and is therefore responsible for poor patient prognosis.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We can predict a similar phenomenon in colorectal cancer as the level of VEGF-C was shown to be elevated in the blood serum of patients with colorectal cancer [19]. It has been hypothesized that lymph node lymph vessels can act as a metastatic niche for cancer cells [7], [8], [20], [21] and facilitate further metastatic transformation of the tumor cells. This might lead to therapy-resistant metastatic cancer and is therefore responsible for poor patient prognosis.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, efforts have been made to uncover the mechanisms of lymph node metastasis. It has been suggested that the induction of lymphangiogenesis in the primary tumor and in lymph nodes significantly contributes to tumor metastases [7], [8]. In this study we have validated lymphangiogenesis in regional lymph nodes as a predictor for poor prognosis and facilitator for distant metastasis in a cohort of neoadjuvant treated advanced rectal cancer patients.…”
Section: Introductionmentioning
confidence: 66%
“…Increased lymphangiogenesis in pancreatic tumors or their draining nodes is generally believed to relate directly to the extent of lymphatic involvement [52, 53]. However, some studies suggest that intratumoral lymphatic vessel density (LVD) is not associated with lymphatic invasion or metastasis [11, 54].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of human pancreatic cancer tissues have identified a role for TALA in lymph node metastasis and patient outcomes. Kurahara, et al [154], found that high lymphatic vessel density (LVD) in PDAC head tumors predicted increased lymph node metastasis and decreased survival. They also showed increased LVD within metastatic lymph nodes [154].…”
Section: Lymphangiogenesismentioning
confidence: 99%
“…Kurahara, et al [154], found that high lymphatic vessel density (LVD) in PDAC head tumors predicted increased lymph node metastasis and decreased survival. They also showed increased LVD within metastatic lymph nodes [154]. Wang, et al , found that increased peritumoral LVD in human pancreatic carcinoma tissues correlated with unfavorable tumor differentiation status, increased LVI, and more lymph node metastasis, while this was not the case for intratumoral LVD [53].…”
Section: Lymphangiogenesismentioning
confidence: 99%